Pharmacokinetic Evaluation of Paracetamol Co-administered with Moringa oleifera and Caesalpinia sappan Extracts Individually in Sprague Dawley Rats - Pradana, Dhigna; Nur, Syifa; Hakim, Annisa Ayu Nur; Rahmi, Eldiza Puji; Muti, Annisa Farida; Abdurrahman Munir, Muhammad (Universitas Ahmad Dahlan, 2026)
Paracetamol is frequently utilized to alleviate pain and fever due to its pharmacological properties as an analgesic and antipyretic. Consuming paracetamol drugs while self-medication might potentially lead to drug interactions when used with other medications, as well as certain foods and herbs. Moringa oleifera and Caesalpinia sappan are popular herbal plants in Indonesia, commonly used to produce herbal food and drinks. These plants contain flavonoids and phenols, which have the potential to impact the metabolism, effectiveness, and toxicity of medications, including paracetamol. This study investigated alterations in the pharmacokinetic characteristics of paracetamol when co-administered with Moringa oleifera and Caesalpinia sappan. The research utilized a true experimental approach with a posttest-only control group design and animal model study is male Sprague-Dawley rats . The control group was administered an oral dose of 9mg/200g body weight of paracetamol. By contrast, the treatment group of male Sprague-Dawley rats was administered an oral dose of 9mg/200g body weight of paracetamol, combined with a dose of 60mg/200g of Moringa leaf extract and sappan heartwood extract at 294 mg/kg body weight. At 30, 60, 120, 180, and 240 minutes, blood samples were collected from the rats' lateral tail vein. Analyzing the concentration of paracetamol in plasma was conducted using a UV-Vis spectrophotometer set at a wavelength of 244 nm. The study showed that combining sappan heartwood extract with paracetamol resulted in a substantial 453.10% increase in the volume of distribution (Vd) (p<0.05). The administration of Moringa leaf extract decreased a little effect the pharmacokinetic profile of paracetamol, as shown by the statistical analysis of the unpaired t-test (p>0.05).